Language, power and ideology - Rahman, Tariq (2002)
Language has been intimately related to ideology and power in Pakistan. While Urdu is conspicuous as a symbol of Pakistani identity and national integration, other ethnic groups have seen this as a version of internal colonialism. Indigenous languages thus become tols that serve to assert ethnic identity and ensure a wider mobilisation. - Reproduced.
Keywords: Languages - Pakistan; Languages